Sopa desidratada de tilápia (Oreochromis niloticus) adicionada de farinha de linhaça (Linum usitatissimum) e reduzido teor de sódio - Patriolino, Fabrínio Marques (2017)
The dehydrated soups found in the market have a low caloric value, but in contrast their sodium content is high, their protein value and fiber content are reduced. The aim of this work was to elaborate and characterize tilapia soups added with different proportions of linseed flour and reduced sodium content through the partial substitution of sodium chloride for potassium chloride. Five formulations of tilapia soup were elaborated that differed as follows: F1 (Control) - Without linseed flour and 4.5 g of NaCl; F2 - 4.47 g linseed flour, 1.8 g NaCl, 2.7 g KCl; F3 - 7.11 g linseed flour, 1.8 g NaCl, 2.7 g KCl; F4 - 4.47 g linseed flour, 2.7 g NaCl, 1.8 g KCl; F5 - 7.11 g linseed flour, 2.7 g NaCl, 1.8 g KCl. To assure the microbiological quality of the formulations the followings determinations were performed: Bacillus cereus, Coliforms at 45ºC, Salmonella sp. and Staphylococcus coagulase positive, where all formulations were in compliance with the standards established by Resolution RDC No. 12/2001, of the National Agency of Sanitary Surveillance - ANVISA. The formulations were submitted to sensory analysis (acceptance test, intention to buy test and ideal scale test) by 60 non trained panelists. The formulation F4 was the one that obtained the best results being dehydrated together with the formulation F1 (control). The physical, physicochemical and chemical characterization of the two formulations were performed through water solubility index (WSI), water absorption index (WAI), centesimal composition, sodium content, crude fiber content and water activity (Wa). No significant difference was observed for the WSI, WAI, Wa and ashes parameters. F4 presented the highest levels of protein (15.49%), total lipids (8.06%), crude fiber (9.13%) and caloric value (357 Kcal.100g-1) while F1 presented the highest levels of sodium 3083 mg.100g-1) and carbohydrates (59.82%). F1 and F4 were submitted to sensory analysis with 50 non trained panelists to evaluate the acceptability of the attributes: color, taste, aroma, creaminess and overall impression in addition to the ideal scale and purchase intention tests, where F4 presented better sensory acceptance in attributes: flavor, aroma, creaminess and overall impression. There was a significant difference (p <0.05) between the formulations in the ideal scale and purchase intention tests, with F4 being more balanced in relation to the salt content and obtaining a more positive intention to buy than F1. Both formulations were evaluated for stability (pH, Wa, color and TBARS) at 0, 15, 30, 45, 60, 75 and 90 days of storage. A significant difference was observed for the parameters: pH (5.70 and 5.32), L* (61.22 and 58.79), a* (10.05 and 9.06) and b* (26.57 and 23.32) of F1 and F4, respectively. There was no significant difference between the formulations for mean values of Wa and TBARS. It was concluded that it is possible to prepare a dehydrated soup of fiber-added and low-sodium tilapia, sensorially accepted and stable at room temperature (25 ° C) for 90 days.